Branched Coverings and Embedded Surfaces in Four-Manifolds (Communications in Mathematical Research, 2021)
In this paper, we get a lower bound on the genera of surfaces representingcertain divisible classes in some 4-manifold $X$ with $H_1(X;Z)$ finite.